Examining the role of community living arrangements in reducing loneliness among young adults in Malaysia - Hoong, Cheah Kim; Mohd Noor, Mohd Zairul; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
In Malaysia, community living arrangements such as co-living and co-housing have emerged as a housing typology in response to rising housing costs, rental trends, and evolving lifestyle preferences among young adults. These arrangements seek to promote social interaction and foster a sense of community and belonging. However, despite their popularity, there is insufficient evidence on the effectiveness of these architectural interventions in addressing loneliness and mental health issues among young adults in Malaysia. Current research on community living models is limited to general concepts and lack empirically backed design strategies tailored to the specific needs and cultural dynamics of young adults. To address this gap, this research aims to develop architectural strategies for community living to foster social cohesion and reduce loneliness among Malaysian young adults, considering their unique cultural and social needs. The research results include a comprehensive framework for community living arrangements and highlighting their effectiveness in improving social connectivity and reducing loneliness. This research will offer data-driven recommendations for policymakers, practical insights for urban planners, and advance architectural design theories.